Molding Spica Casts to Maintain Alignment of Femur Fractures. Issue 5 (May 2018) - Nielsen, Ena; Skaggs, David L.; Ryan, Deirdre; Andras, Lindsay M.
Abstract : Background: Femur fractures in young children are frequently treated with spica casting. Texts recommend molding spica casts into valgus and recurvatum to counter deforming muscular forces, but how much overcorrection to aim for has not been evaluated. Our goal was to determine how much valgus and recurvatum is optimal at the time of casting to end up with anatomic alignment. Methods: Patients 1 to 6 years old with femur fractures treated with spica casts between January 1, 2008 and January 31, 2014 who were followed until radiographic union were included in the study. Patients with underlying medical comorbidities affecting bone quality, refractures, or preexisting femur deformities or that did not have intraoperative imaging were excluded. Results: A total of 52 patients met the inclusion criteria. Average intraoperative angulation was 2.6 degrees of valgus (range: 9 degrees varus to 13 degrees valgus, SD: 4.5) and 1.1 degrees of recurvatum (range: 10 degrees recurvatum to 17 degrees procurvatum, SD: 4.8). At the initial postoperative visit, the average angulation was 2.7 degrees of varus (range: 21 degrees varus to 11degrees valgus, SD: 6.4) and 7.2 degrees of procurvatum (range: 6 degrees recurvatum to 25 degrees procurvatum, SD: 6.6). At the time of radiographic union/wedging average angulation was 2.0 degrees of varus (range: 15 degrees varus to 10 degrees valgus, SD: 5.8) and 8.5 degrees of procurvatum (range: 5 degrees recurvatum to 29 degrees procurvatum, SD: 7.5). Between the intraoperative period to time of union or wedging, fracture alignment gained an average of 4.6 degrees of varus (range: 17 degrees varus to 13 degrees valgus, SD: 6.6) and 9.8 degrees of procurvatum (range: 8 degrees recurvatum to 30 degrees procurvatum, SD: 9.1). Seven patients underwent cast wedging due to loss of reduction before radiographic union, 2 patients underwent reoperation due to excessive angulation in the early postoperative period, and 5 patients developed malunions. Conclusion: Femur fractures treated with spica casts gain 5 degrees of varus and 10 degrees of procurvatum between cast application and fracture union. Level of Evidence: Level IV.